Patch preparation
By adding drugs, levulinic acid and propylene glycol fatty acid ester to the adhesive layer of the skin patch, the problems of insufficient absorption and poor adhesion of existing patches are solved, and efficient penetration of the skin and good adhesion are achieved.
Patent Information
- Application Number
- JP2022501955
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-19
- Filing Date
- 2021-02-18
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2041-02-18
AI Technical Summary
Existing skin patches are difficult to effectively penetrate the skin, resulting in insufficient absorption of drugs, and poor adhesion and inconvenient use.
Add drugs, levulinic acid and propylene glycol fatty acid ester to the adhesive layer of the patch to improve the skin penetration and adhesion of the drug through these ingredients.
It achieves efficient penetration of the drug through the skin and good adhesion, reducing skin irritation and inconvenience during use.
Smart Images

Figure 0007667771000009 
Figure 0007667771000001 
Figure 0007667771000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a patch preparation containing a drug, levulinic acid, and a propylene glycol fatty acid ester. [Background technology]
[0002] Transdermal preparations such as patch preparations are not only intended to treat lesions on the skin surface or in tissues immediately below the skin application site through local drug absorption, but are also used as preparations that are expected to have a systemic effect by directly taking up the drug that has permeated the skin into the capillaries below the skin. Transdermal administration of drugs using such patch preparations can avoid the first-pass effect in the liver, thereby preventing overdosage of drugs, and also has the advantage that when the transdermal administration of drugs is to be discontinued, the administration of the drug can be discontinued simply and safely by peeling off the patch preparation from the applied skin surface.
[0003] However, since the skin, which is the application site of a patch preparation, has a barrier function that prevents the intrusion of foreign substances from the outside, it is often difficult for a necessary and sufficient amount of drug to permeate through the skin in order to exert the efficacy of the drug. For this reason, various efforts have been made to improve the transdermal permeability of drugs.
[0004] For example, it has been thought that the skin permeability of a drug can be improved by increasing the planar area of a patch preparation, but this has led to problems such as ease of handling (difficulty in applying to the skin, difficulty in reapplying, etc.) and the tendency for the patch to become stuffy or itchy during application to the skin (Patent Document 1). Attempts to improve the skin permeability of a drug by incorporating a transdermal absorption enhancer into the patch preparation have also been considered, but depending on the drug, it may be difficult to achieve sufficient skin permeability, or depending on the type of transdermal absorption enhancer, adverse effects such as a decrease in the adhesive properties (cohesion, etc.) of the patch preparation may occur (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 10-251145 [Patent Document 2] Japanese Patent Application Publication No. 7-247221 Summary of the Invention [Problem to be solved by the invention]
[0006] In view of the above circumstances, an object of the present invention is to provide a patch preparation which is excellent in drug skin permeability and has good adhesive properties. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted extensive research in order to achieve the above-mentioned object, and as a result have found that by incorporating a drug (excluding tandospirone or a pharma- ceutical acceptable salt thereof), levulinic acid, and a propylene glycol fatty acid ester in the adhesive layer of a patch preparation, it is possible to impart practical adhesive properties and drug skin permeability as a transdermal absorption preparation, and also to reduce skin irritation during peeling, thereby completing the present invention.
[0008] The present invention is as follows. [1] A patch preparation having an adhesive layer on at least one surface of a support, A patch preparation, characterized in that the adhesive layer contains a drug (excluding tandospirone or a pharma- ceutically acceptable salt thereof), levulinic acid, and a propylene glycol fatty acid ester (hereinafter, also referred to as "the patch preparation of the present invention"). [2] The patch preparation according to the above-mentioned [1], wherein the propylene glycol fatty acid ester is an ester of propylene glycol and a saturated or unsaturated fatty acid having 8 to 18 carbon atoms. [3] The patch preparation according to the above-mentioned [1] or [2], wherein the propylene glycol fatty acid ester is propylene glycol monocaprylate or propylene glycol monolaurate. [4] The patch preparation according to any one of the above-mentioned [1] to [3], wherein the adhesive layer further contains a fatty acid ester other than propylene glycol fatty acid ester. [5] The patch preparation according to the above-mentioned [4], wherein the other fatty acid ester is at least one selected from the group consisting of esters of alcohols having a linear or branched alkyl group or cyclic alkyl group having 1 to 18 carbon atoms and saturated or unsaturated fatty acids having 8 to 18 carbon atoms, and esters of glycerin and saturated or unsaturated fatty acids having 8 to 18 carbon atoms. [6] The patch preparation according to any one of the above-mentioned [1] to [5], wherein the content of the propylene glycol fatty acid ester in 100% by mass of the adhesive layer is 1 to 30% by mass. [7] The patch preparation according to any one of the above-mentioned [1] to [6], wherein the content ratio of levulinic acid to propylene glycol fatty acid ester is 1:0.1 to 1:20 by mass ratio. [8] The patch preparation according to any one of the above-mentioned [1] to [7], wherein the adhesive base constituting the adhesive layer is an acrylic polymer. [9] The patch preparation according to any one of the above-mentioned [1] to [8], wherein the drug is a basic drug having a basic group.
[10] The patch preparation according to any one of the above-mentioned [1] to [9], wherein the logPow of the drug is -1 to 7. Effect of the Invention
[0009] According to the present invention, a patch preparation having excellent skin permeability of a drug and good adhesive properties (cohesive strength, water-resistant adhesiveness, etc.) can be provided. [Brief description of the drawings]
[0010] [Figure 1] Figure 1 shows the measurement method for the underwater constant-load peel test of a patch preparation, (a) being a schematic perspective view thereof, and (b) being a schematic front view thereof. Note that the dimensions and dimensional ratios in the figure are exaggerated for the sake of explanation, and may differ from the actual ratios. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Preferred embodiments of the present invention will be described below, but the present invention is not limited to these specific embodiments.
[0012] Adhesive layer The patch preparation of the present invention is characterized in that it contains a drug, levulinic acid, and a propylene glycol fatty acid ester in the adhesive layer.
[0013] (Drugs) The drug in the patch preparation of the present invention is not particularly limited as long as it is a drug that can be administered to a mammal such as a human through the skin (i.e., a drug that can be absorbed transdermally), except for tandospirone or a pharma- ceutically acceptable salt thereof. Examples of such drugs include general anesthetics, hypnotics / sedatives, antiepileptics, antipyretics / analgesics / anti-inflammatory drugs, antivertigo drugs, psychoneurotic drugs, central nervous system drugs, antidementia drugs, local anesthetics, skeletal muscle relaxants, autonomic nervous system drugs, antispasmodics, antiparkinsonian drugs, antihistamines, cardiac stimulants, antiarrhythmic drugs, diuretics, antihypertensive drugs, vasoconstrictors, coronary vasodilators, peripheral vasodilators, arteriosclerosis drugs, circulatory system drugs, respiratory stimulants, antitussives and expectorants, hormonal drugs, external drugs for suppurative diseases, analgesics / antipruritics / astringents / anti-inflammatory drugs, drugs for parasitic skin diseases, hemostatic drugs, drugs for the treatment of gout, drugs for diabetes, anti-malignant tumor drugs, antibiotics, chemotherapy drugs, narcotics, smoking cessation aids, and the like.
[0014] The drug may be in the form of a free base, or in the form of a pharmaceutically acceptable salt. The pharmaceutically acceptable salt includes, but is not limited to, addition salts of organic acids such as formate, acetate, lactate, adipate, citrate, tartrate, methanesulfonate (also called mesylate), benzenesulfonate (also called besylate), fumarate, maleate, etc.; addition salts of inorganic acids such as hydrochloride, sulfate, nitrate, phosphate, etc.; addition salts of organic bases such as meglumine salt, piperazine salt, tromethamine salt, choline salt, diethylamine salt, tert-butylamine salt, etc.; addition salts of inorganic bases such as sodium salt, calcium salt, potassium salt, magnesium salt, aluminum salt, ammonium salt, etc.; and the like. The drug may be a solvate (e.g., hydrate, ethanol solvate, propylene glycol solvate) or a non-solvate.
[0015] As the drug in the patch preparation of the present invention, it is preferable to use a basic drug having a basic group. Examples of such drugs include drugs having at least one functional group selected from the group consisting of an alcoholic hydroxyl group, a sulfanyl group, a phenolic hydroxyl group, and an amino group (e.g., a primary amino group (-NH2), a secondary amino group (-NRH), and a tertiary amino group (-NRR'); where R and R' each independently represent an optionally substituted alkyl group or an optionally substituted aryl group).
[0016] The partition coefficient (1-octanol / water) of the drug in the patch preparation of the present invention, i.e., the lower limit of logPow, is preferably -1, more preferably 0, and even more preferably 1, and the upper limit of logPow is preferably 7, more preferably 6, and even more preferably 5. When the logPow of the drug is in the range of -1 to 7, the drug dispersibility in the adhesive layer is excellent.
[0017] Here, logPow is an index representing the hydrophilicity or hydrophobicity of a drug, and refers to a value measured for each drug by the method described in "OECD GUIDELINE FOR THE TESTING OF CHEMICALS 107, Adopted by the Council on 27th July 1995, Partition Coefficient (n-octanol / water), Shake Flask Method", and the logarithm of logPow has a base of 10. In this embodiment, logPow was calculated using a logP calculation software (Scigress, Fujitsu Ltd.). When measuring (calculating) logPow, the structural formula of the compound is input into the calculation software, and logPow is calculated.
[0018] The content of the drug in the adhesive layer is not particularly limited as long as the drug exerts its effect and does not cause side effects, but the lower limit of the drug content is preferably 0.1% by mass, more preferably 0.5% by mass, and even more preferably 1% by mass, based on 100% by mass of the adhesive layer. The upper limit of the drug content is preferably 50% by mass, more preferably 40% by mass, and even more preferably 30% by mass, based on 100% by mass of the adhesive layer. If the drug content is less than 0.1% by mass, sufficient efficacy may not be obtained, and conversely, if the drug content exceeds 50% by mass, side effects due to the drug (for example, skin irritation during application) may occur.
[0019] (Levulinic acid) The levulinic acid used in the present invention is an organic acid classified as a keto acid. The levulinic acid may be in the form of a free acid (i.e., levulinic acid itself) or in the form of a pharma- ceutically acceptable salt thereof. Examples of the pharma-ceutically acceptable salt include alkali metal salts such as sodium salts. As the levulinic acid, a commercially available product may be used as it is, or a pharma-ceutically acceptable salt thereof prepared from levulinic acid according to a method known per se may be used. As the levulinic acid used in the present invention, levulinic acid in the form of a free acid may be used.
[0020] The content of levulinic acid in the adhesive layer is not particularly limited, but the upper limit of the content of levulinic acid is preferably 30% by mass, more preferably 20% by mass, and even more preferably 15% by mass, based on 100% by mass of the adhesive layer. The lower limit of the content of levulinic acid is preferably 0.1% by mass, more preferably 0.5% by mass, and even more preferably 1% by mass, based on 100% by mass of the adhesive layer. If the content of levulinic acid in the adhesive layer is less than 0.1% by mass, it becomes difficult to obtain necessary and sufficient skin permeability of the drug. On the other hand, if the content of levulinic acid in the adhesive layer exceeds 30% by mass, the shape retention of the adhesive layer decreases, and glue overflow occurs during storage of the patch preparation, or glue residue may occur on the skin surface when the patch preparation is peeled off from the skin surface after application of the patch preparation.
[0021] (Propylene glycol fatty acid ester) The propylene glycol fatty acid ester used in the present invention is an ester of propylene glycol and a saturated or unsaturated fatty acid having 8 to 18 carbon atoms, and examples thereof include propylene glycol mono fatty acid ester, propylene glycol di fatty acid ester, etc. Specific examples of propylene glycol fatty acid ester include propylene glycol monocaprylate, propylene glycol monocaprate, propylene glycol monolaurate, propylene glycol monostearate, propylene glycol monooleate, propylene glycol dicaprylate, propylene glycol dicaprate, propylene glycol dicaprylate / dicaprate (propylene glycol dicaprylocaprate), propylene glycol dilaurate, propylene glycol distearate, propylene glycol diisostearate, propylene glycol dioleate, etc. Among them, esters of propylene glycol and a saturated or unsaturated fatty acid having 8 to 14 carbon atoms are preferred, and propylene glycol monocaprylate or propylene glycol monolaurate is more preferred. These propylene glycol fatty acid esters can be used alone or in combination of two or more.
[0022] The content of the propylene glycol fatty acid ester in the adhesive layer is not particularly limited, but the upper limit of the content of the propylene glycol fatty acid ester is preferably 30% by mass, more preferably 25% by mass, and even more preferably 20% by mass, based on 100% by mass of the adhesive layer. The lower limit of the content of the propylene glycol fatty acid ester is preferably 1% by mass, more preferably 2% by mass, and even more preferably 3% by mass, based on 100% by mass of the adhesive layer.
[0023] Furthermore, the content ratio of levulinic acid to propylene glycol fatty acid ester in the adhesive layer (levulinic acid:propylene glycol fatty acid ester) is, by mass, preferably in the range of 1:0.1 to 1:20, more preferably 1:0.2 to 1:15, even more preferably 1:0.3 to 1:10, and particularly preferably 1:0.5 to 1: 10. If the content of propylene glycol fatty acid ester and the content ratio of levulinic acid to propylene glycol fatty acid ester in the adhesive layer are outside the above ranges, it becomes difficult to achieve both good skin permeability of the drug and practical adhesive properties (cohesive strength, water-resistant adhesion, etc.).
[0024] (Other fatty acid esters) In the patch preparation of the present invention, it is preferable that the adhesive layer further contains other fatty acid esters than propylene glycol fatty acid esters. Examples of such other fatty acid esters include fatty acid alkyl esters (esters of alcohols having a linear or branched alkyl group or a cyclic alkyl group having 1 to 18 carbon atoms and saturated or unsaturated fatty acids having 8 to 18 carbon atoms) such as ethyl laurate, isostearyl laurate, isopropyl myristate, isotridecyl myristate, isopropyl palmitate, octyl palmitate, and ethyl oleate; and glycerin fatty acid esters (esters of glycerin and saturated or unsaturated fatty acids having 8 to 18 carbon atoms) such as glyceryl monocaprylate, glyceryl tricaprylate, glyceryl tri-2-ethylhexanoate, glyceryl tricaprate, glyceryl trilaurate, glyceryl triisostearate, and glyceryl trioleate. These other fatty acid esters can be used alone or in combination of two or more.
[0025] The content of the other fatty acid ester in the adhesive layer is not particularly limited, but the upper limit of the content of the other fatty acid ester in 100% by mass of the adhesive layer is preferably 85% by mass, more preferably 80% by mass, and even more preferably 75% by mass. The lower limit of the content of the other fatty acid ester in 100% by mass of the adhesive layer is preferably 5% by mass, more preferably 7.5% by mass, and even more preferably 10% by mass.
[0026] (Adhesive base) The adhesive layer in the patch preparation of the present invention is preferably an adhesive layer containing a non-aqueous adhesive base in order to exhibit good skin adhesion. Such a non-aqueous adhesive layer is not limited to one that is completely free of moisture, but includes one that contains a small amount of moisture (e.g., less than 1% by mass in the adhesive layer) derived from moisture in the air or skin, etc.
[0027] The adhesive base means a polymer constituting the matrix of the adhesive layer. The adhesive base is mixed with a tackifier (tackifier) described below as necessary to form the adhesive. Only one type of adhesive base may be used, or two or more types may be used in combination. Examples of non-aqueous adhesive bases include acrylic polymers such as (meth)acrylic acid ester polymers; rubber polymers such as styrene-isoprene-styrene block copolymers, styrene-butadiene-styrene block copolymers, polyisoprene, polyisobutylene, and polybutadiene; and silicone polymers such as silicone rubber, dimethylsiloxane base, and diphenylsiloxane base. Among such non-aqueous adhesive bases, it is preferable to include an acrylic polymer because it is easy to adjust the release of drugs and the adhesive strength, and it is less irritating to the skin. Such an acrylic polymer is not particularly limited, but for example, an acrylic polymer obtained from a monomer mixture containing a (meth)acrylic acid alkyl ester monomer is preferably used. In this specification, "(meth)acrylic" means both "acrylic" and "methacrylic".
[0028] The (meth)acrylic acid alkyl ester monomer (hereinafter, sometimes referred to as "first monomer") is not particularly limited, but from the viewpoint of adhesion, a (meth)acrylic acid alkyl ester monomer having an alkyl group having 4 or more carbon atoms is preferable. Examples of such (meth)acrylic acid alkyl ester monomers include (meth)acrylic acid alkyl ester monomers in which the alkyl group is a straight chain alkyl group or a branched chain alkyl group having 4 to 13 carbon atoms, such as n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, n-pentyl group, isopentyl group, neopentyl group, hexyl group, heptyl group, octyl group, 2-ethylhexyl group, nonyl group, decyl group, undecyl group, dodecyl group, and tridecyl group. Among them, butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferable, and 2-ethylhexyl acrylate is particularly preferable. These (meth)acrylic acid alkyl ester monomers can be used alone or in combination of two or more.
[0029] In addition, the acrylic polymer is preferably an acrylic polymer obtained by copolymerizing a monomer mixture containing an N-vinyl cyclic amide (hereinafter, also referred to as "second monomer") in addition to a (meth)acrylic acid alkyl ester monomer. Examples of such N-vinyl cyclic amides include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione. Among them, N-vinyl-2-pyrrolidone is particularly preferred. These N-vinyl cyclic amides can be used alone or in combination of two or more.
[0030] When N-vinyl cyclic amide is contained as a monomer component constituting the acrylic polymer, its content in the acrylic polymer is preferably 75% by mass or less, more preferably 1-75% by mass, even more preferably 5-75% by mass, particularly preferably 10-70% by mass, and most preferably 15-65% by mass. By copolymerizing N-vinyl cyclic amide, the adhesive strength and cohesive strength of the patch preparation can be adjusted, and the solubility of the drug in the adhesive layer and the release of the drug from the adhesive layer can be adjusted. If the content of N-vinyl cyclic amide in the acrylic polymer exceeds 75% by mass, the tack and adhesive strength of the obtained patch preparation may decrease.
[0031] The acrylic polymer may be an acrylic polymer obtained by copolymerizing a monomer mixture containing a monomer having another functional group (hereinafter, sometimes referred to as a "third monomer") as a monomer component constituting the acrylic polymer. Examples of such other functional groups include a carboxyl group, a hydroxyl group, and a vinyl group, and among these, a carboxyl group and a hydroxyl group are preferable. Specific examples of monomers having other functional groups include (meth)acrylic acid, itaconic acid, (anhydride) maleic acid, mesaconic acid, citraconic acid, glutaconic acid, (meth)acrylic acid hydroxyethyl ester, (meth)acrylic acid hydroxypropyl ester, and N-hydroxyalkyl (meth)acrylamide. The N-hydroxyalkyl (meth)acrylamide is preferably N-hydroxyalkyl (C1-4) (meth)acrylamide in which the alkyl group has 1 to 4 carbon atoms, and more preferably N-hydroxyalkyl (C2-4) acrylamide in which the alkyl group has 2 to 4 carbon atoms. The alkyl group in the hydroxyalkyl group may be linear or branched. Specific examples of N-hydroxyalkyl(meth)acrylamides include N-(2-hydroxyethyl)acrylamide, N-(2-hydroxyethyl)methacrylamide, N-(2-hydroxypropyl)acrylamide, N-(2-hydroxypropyl)methacrylamide, N-(1-hydroxypropyl)acrylamide, N-(1-hydroxypropyl)methacrylamide, N-(3-hydroxypropyl)acrylamide, N-(3-hydroxypropyl)methacrylamide, N-(2-hydroxybutyl)acrylamide, N-(2-hydroxybutyl)methacrylamide, N-(3-hydroxybutyl)acrylamide, N-(3-hydroxybutyl)methacrylamide, N-(4-hydroxybutyl)acrylamide, and N-(4-hydroxybutyl)methacrylamide. As the monomer having another functional group, acrylic acid, methacrylic acid, hydroxyethyl acrylate, N-(2-hydroxyethyl)acrylamide, and N-(2-hydroxyethyl)methacrylamide are preferred, and acrylic acid, hydroxyethyl acrylate, and N-(2-hydroxyethyl)acrylamide are more preferred.These monomers having other functional groups can be used alone or in combination of two or more.
[0032] When the acrylic polymer is a copolymer of an alkyl (meth)acrylate ester (first monomer), an N-vinyl cyclic amide (second monomer), and a monomer having another functional group (third monomer), the copolymerization ratio (first monomer / second monomer / third monomer) is preferably 20 to 90 mass% / 5 to 75 mass% / 1 to 15 mass%, more preferably 25 to 85 mass% / 10 to 70 mass% / 1 to 10 mass%, and particularly preferably 30 to 80 mass% / 15 to 65 mass% / 1 to 10 mass%.
[0033] The acrylic polymer can be obtained by a known polymerization method such as a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, etc. Alternatively, the acrylic polymer can be obtained by radical polymerization using a radical polymerization initiator such as a peroxide compound (e.g., benzoyl peroxide, etc.) or an azo compound (e.g., azobisisobutyronitrile, etc.).
[0034] When the adhesive base is insufficient in adhesion at room temperature, a tackifier (adhesive imparting agent) may be further blended to impart adhesion at room temperature to the adhesive layer. In addition to the case where a rubber-based polymer is used as the adhesive base, even when an acrylic-based polymer is used, a tackifier may be further blended to enhance the adhesion of the adhesive layer. As the tackifier, a known one in the field of patch preparations can be appropriately selected and used. Specific examples of tackifiers include petroleum-based resins (e.g., aromatic petroleum resins, aliphatic petroleum resins, etc.), terpene-based resins, rosin-based resins, coumarone-indene resins, styrene-based resins (e.g., styrene resins, poly(α-methylstyrene), etc.), hydrogenated petroleum resins (e.g., alicyclic saturated hydrocarbon resins, etc.), etc. Among these, alicyclic saturated hydrocarbon resins are preferred because they improve the storage stability of the drug. When a tackifier is used, its content in the adhesive layer is usually 30 parts by mass or more and less than 100 parts by mass, preferably 50 parts by mass or more and less than 100 parts by mass, per 100 parts by mass of the adhesive base.
[0035] (Crosslinking agent) In the patch preparation of the present invention, in order to impart an appropriate cohesive force to the adhesive layer, a crosslinking treatment can be carried out as necessary. Examples of the crosslinking treatment include physical crosslinking treatment (e.g., crosslinking treatment by gamma-ray irradiation, electron beam irradiation, etc.) and chemical crosslinking treatment (e.g., crosslinking treatment by a crosslinking agent such as an organic peroxide, an isocyanate compound, an organic metal salt, a metal alcoholate, a metal chelate compound, an epoxy compound, a primary amino group-containing compound, etc.). Specific examples of the chemical crosslinking treatment include crosslinking treatment by a crosslinking agent such as an organic peroxide such as benzoyl peroxide, an isocyanate compound such as tolylene diisocyanate, hexamotylene diisocyanate, etc., an epoxy compound such as glycerin triglycidyl ether, triglycidyl isocyanurate, etc., and a metal chelate compound such as aluminum tris(acetylacetonate), aluminum ethyl acetoacetate diisopropylate, etc. Among these crosslinking agents, it is preferable to use an isocyanate compound, a metal alcoholate, or a metal chelate compound in terms of crosslinking reactivity and ease of handling. Such a crosslinking treatment makes it possible to suitably adjust the balance between the flexibility of the pressure-sensitive adhesive layer and adhesive properties such as cohesive strength, thereby making it possible to suppress adhesive residue upon peeling.
[0036] The amount of crosslinking agent blended can be adjusted appropriately depending on the type of adhesive base and crosslinking agent, but is preferably 0.03 to 2.0 parts by mass, more preferably 0.05 to 1.5 parts by mass, and even more preferably 0.07 to 1.0 part by mass, per 100 parts by mass of the adhesive base to be crosslinked (in the case of an acrylic polymer).
[0037] (Other ingredients (additives)) The adhesive layer in the patch preparation of the present invention may contain various additives such as fragrances, colorants, plasticizers, softeners, fillers, stabilizers, antioxidants, antibacterial agents, bactericides, etc., as necessary, within the scope of not impairing the effects of the present invention. As the additives, those known in the field of patch preparations can be appropriately selected and used.
[0038] In the patch preparation of the present invention, the upper limit of the thickness of the adhesive layer is preferably 500 μm, more preferably 400 μm, and even more preferably 300 μm. The lower limit of the thickness of the adhesive layer is preferably 10 μm, more preferably 20 μm, and even more preferably 30 μm. If the thickness of the adhesive layer is less than 10 μm, it becomes difficult to obtain sufficient adhesive properties, while if the thickness of the adhesive layer is more than 500 μm, there is a risk of glue overflow during storage of the patch preparation.
[0039] support The support constituting the patch preparation of the present invention is not particularly limited as long as it can form and hold an adhesive layer on one side. Examples of the material of the support include polyester (e.g., polyethylene terephthalate (PET), etc.), polyamide (e.g., nylon, etc.), polyethylene, polypropylene, polyvinyl chloride, polyvinylidene chloride (trade name: Saran, etc.), ionomer resin (trade name: Surlyn, etc.), polytetrafluoroethylene, ethylene-ethyl acrylate copolymer, ethylene-vinyl alcohol copolymer (trade name: EVAL, etc.), various metals, etc. The support may be a single layer of various plastic films or various metal foils made of the above materials, or a laminate thereof. In addition, in order to improve the anchoring property with the adhesive layer formed on the support, the surface of the support may be treated with an undercoat layer, corona discharge treatment, plasma irradiation treatment, primer treatment, etc.
[0040] Furthermore, in order to improve the anchoring property of the support with the pressure-sensitive adhesive layer, a laminate in which a porous sheet is laminated on the pressure-sensitive adhesive layer side of the support can be used.Specific examples of such porous sheets include fiber aggregates such as paper, knitted fabric, woven fabric, and nonwoven fabric (e.g., polyester nonwoven fabric, polyethylene terephthalate nonwoven fabric, etc.), as well as single-layer bodies (single-layer films) such as the above-mentioned plastic films, and sheets mechanically perforated on laminate films in which one or more of these films are laminated, and among these, paper, woven fabric, and nonwoven fabric (e.g., polyester nonwoven fabric, polyethylene terephthalate nonwoven fabric, etc.) are preferred.
[0041] The thickness of the backing is preferably 10 to 200 μm, more preferably 10 to 100 μm, from the viewpoints of improving anchoring properties, flexibility of the patch preparation, ease of application, etc. When a woven fabric or nonwoven fabric is used as the porous sheet, the basis weight of the fabric is preferably 5 to 30 g / m 2 and more preferably 6 to 15 g / m 2 It is.
[0042] Release Liner In the patch preparation of the present invention, the surface of the adhesive layer opposite to the support (the surface to be applied to the skin) is preferably laminated with a release liner until the preparation is actually used. The release liner is not particularly limited as long as it has good releasability when used. Specific examples include plastic films such as polyester, polyvinyl chloride, polyvinylidene chloride, polyethylene terephthalate, etc., which have been subjected to release treatment by applying silicone resin, fluororesin, etc. to the surface that contacts the adhesive layer, papers such as fine paper, glassine paper, etc., and laminate films of paper such as fine paper, glassine paper, etc. and polyolefin (the side that contacts the adhesive layer is paper), etc.
[0043] The thickness (total thickness) of the release liner is not particularly limited, but is preferably 10 to 200 μm, and more preferably 25 to 100 μm.
[0044] The size of the patch preparation of the present invention is not particularly limited, but is usually 1 to 300 cm. 2 and preferably 2 to 200 cm 2 More preferably, it is 3 to 100 cm 2 The patch preparation of the present invention is usually replaced at a frequency of 3 times / day to once every two weeks, preferably 2 times / day to once every week, more preferably 1 time / day to once every week, and even more preferably 1 time / day to once every four days.
[0045] Method for producing the patch preparation of the present invention The method for producing the patch preparation of the present invention is not particularly limited, but it can be produced, for example, by the following production method.
[0046] The adhesive base material containing an acrylic polymer, the drug, levulinic acid and propylene glycol fatty acid ester are added to a suitable solvent together with other additives as necessary, and mixed thoroughly until homogeneous. Examples of the solvent include ethyl acetate, toluene, hexane, 2-propanol, methanol, ethanol, water, etc. Then, when a crosslinking agent is added, the crosslinking agent is further added to this mixture and mixed thoroughly. At this time, a solvent may be added together with the crosslinking agent and mixed as necessary.
[0047] Next, the obtained mixture is applied to one side of a support or the release-treated surface of a release liner, and dried to form an adhesive layer. The application can be performed by, for example, casting, printing, or other techniques known to those skilled in the art. Then, a release liner or a support is attached to the adhesive layer to form a laminate. When crosslinking is performed, the release liner or support is attached to the adhesive layer, and then the adhesive layer is left to stand for 8 to 48 hours, usually at room temperature to 120°C, preferably at room temperature to 100°C, to promote the crosslinking reaction, forming a crosslinked adhesive layer. EXAMPLES
[0048] The effects of the present invention will be described in more detail below with reference to examples, comparative examples, and test examples, but the present invention is not limited thereto. In the following, "parts" and "%" mean "parts by mass" and "% by mass", respectively. In addition, room temperature means a temperature of 15°C to 30°C, unless otherwise specified.
[0049] [Preparation of acrylic polymer (A)] Under an inert gas atmosphere, 55 parts by mass of 2-ethylhexyl acrylate, 40 parts by mass of N-vinyl-2-pyrrolidone, 5 parts by mass of N-(2-hydroxyethyl)acrylamide, and 0.2 parts by mass of 2,2'-azobisisobutyronitrile were solution-polymerized in ethyl acetate (60°C) to prepare a solution of acrylic polymer (A).
[0050] [Manufacturing of patch preparations] (Examples 1 to 2, Comparative Examples 1 to 5) The solution of acrylic polymer (A) was applied to the release-treated surface of a polyester release liner (thickness: 75 μm) so that the thickness after drying would be 100 μm, and dried at 100° C. for 3 minutes to form an adhesive layer. The formed adhesive layer was punched out to 3 mm in diameter, and then 5 μL of the mixed solution shown in Table 1 was impregnated into the adhesive layer to obtain a patch preparation. The content (mass%) of each component in the patch preparation is as shown in Table 2.
[0051] [Table 1]
[0052] [Table 2]
[0053] [Skin permeability test 1] The above 3 mmφ patch preparation was applied to the stratum corneum surface of the skin (intact skin) excised from the abdomen or back of a hairless mouse after removing the release liner. The excised skin with the patch preparation attached and fixed was attached to a permeability test device, and the receptor liquid was sampled after 48 hours, and the amount of drug permeated through the skin was calculated using an ultra-high performance high resolution liquid chromatograph (UPLC). As the receptor liquid, 40 g of bovine serum albumin was dissolved in 1 L of phosphate buffered saline, and the temperature was set at 32°C. The results of the amount of drug permeated through the skin in skin permeability test 1 are shown in Table 3.
[0054] [Table 3]
[0055] The results in Table 3 show that the patch preparations of Examples 1 and 2 have significantly higher skin permeability of the drug than the patch preparations of Comparative Examples 1-5.
[0056] [Preparation of acrylic polymer (B)] Under an inert gas atmosphere, 72 parts by mass of 2-ethylhexyl acrylate, 25 parts by mass of N-vinyl-2-pyrrolidone, 3 parts by mass of acrylic acid, and 0.2 parts by mass of 2,2'-azobisisobutyronitrile were solution-polymerized in ethyl acetate (60°C) to prepare a solution of acrylic polymer (B).
[0057] [Manufacturing of patch preparations] (Examples 3 to 14, Comparative Examples 6 to 29) A solution of the drug, isopropyl myristate (IPM), propylene glycol fatty acid ester (PG fatty acid ester), organic acid, and acrylic polymer (B) was added to a container and stirred to make it uniform, aluminum ethyl acetoacetate diisopropylate (ALCH) was added, and the viscosity was adjusted with ethyl acetate. The obtained solution was applied to the release-treated surface of a polyester release liner (thickness: 75 μm) so that the thickness after drying was 100 μm, and the adhesive layer was formed by drying at 100° C. for 3 minutes. The adhesive layer thus formed was then applied to a 2 μm-thick polyester film and a polyester nonwoven fabric (basis weight: 12 g / m 2 The content (mass %) of each component in the patch preparation is as shown in Tables 4 and 5.
[0058] [Table 4]
[0059] [Table 5]
[0060] [Skin permeability test 2] The patch preparations of Examples 3 to 14 and Comparative Examples 6 to 29 were punched out to 6 mmφ and the release liner was peeled off and removed, and the adhesive layer surface of the patch preparation was attached to the stratum corneum surface of the skin (intact skin) excised from the abdomen or back of a hairless mouse. The excised skin with the patch preparation attached and fixed was attached to a permeability test device, and the receptor liquid was sampled after 24 hours, and the amount of drug permeated through the skin was calculated using an ultra-performance high-resolution liquid chromatograph (UPLC). Phosphate buffered saline (9.6 g / L) was used as the receptor liquid, and the temperature was set to 32°C.
[0061] [Cohesion test] After peeling off the release liners from the patch preparations of Examples 3 to 14 and Comparative Examples 6 to 29, the exposed surface of the adhesive layer was pressed with a finger for approximately 1 second, and when the finger was removed from the adhesive layer, the condition of the adhesive layer and the surface of the finger were visually evaluated using the following index. 〇: No stringiness, no glue residue on fingers ×: Stringiness occurs and glue remains on fingers.
[0062] [Underwater constant load peel test] The underwater constant load peel test will be described with reference to FIG. A collagen membrane 22 (width 25 mm, length 100 mm, thickness 38 μm) was attached to a bakelite plate 23 (width 30 mm, length 130 mm, thickness 2 mm) via a double-sided tape (not shown) to prepare a test plate. Next, the patch preparation 21 was cut into a rectangle of width 10 mm and length 40 mm, the release paper was peeled off to expose the adhesive layer surface, and the adhesive layer surface was pressed and attached to the collagen membrane 22 of the test plate by rolling it back and forth with a 2 kg rubber roller once to obtain a test sample. After 10 minutes at room temperature in this state, a support 27 having the shape shown in FIG. 1 was placed in a water tank 25 containing water 24 at 40°C, and a test sample was placed so that the two separated ends of the bakelite plate 23 were placed on the support 27 in the state shown in FIG. 1, and a weight 26 of 10 g was hung on one end of the patch preparation 21, and the distance and time at which the patch preparation 21 peeled off were measured. The same test was repeated three times, and the peeling speed was calculated from the following formula (1). The average value was taken and this was calculated as the value in the underwater constant load peeling test. The smaller this value, the more difficult it is to peel in water.
[0063]
number
[0064] The results of the skin permeability test 2, the cohesive strength test, and the underwater constant load peel test are shown in Tables 6 and 7.
[0065] [Table 6]
[0066] [Table 7]
[0067] The patch preparations containing levulinic acid and PGML (Examples 3 to 6, Examples 9 to 11) had higher skin permeation and showed good adhesive properties (cohesive strength, water-resistant adhesion) compared to patch preparations containing levulinic acid but not PGML (Comparative Example 6, Comparative Example 18) and patch preparations containing PGML but not levulinic acid (Comparative Example 7, Comparative Example 19). Similarly, the patch preparations containing levulinic acid and PGMC (Examples 7 to 8, Examples 12 to 14) had higher skin permeation amounts and showed good adhesive properties (cohesive strength, water-resistant adhesion) compared to patch preparations containing levulinic acid but not PGMC (Comparative Example 13, Comparative Example 24) and patch preparations containing PGMC but not levulinic acid (Comparative Example 14, Comparative Example 25). In addition, the patch preparations in which lactic acid was used instead of levulinic acid (Comparative Examples 8 to 12, 15 to 17, 20 to 23, and 26 to 29) exhibited a stringy phenomenon in the cohesion test, and therefore could not be used from the viewpoint of adhesive properties. [Industrial Applicability]
[0068] According to the present invention, by incorporating a drug, levulinic acid, and a propylene glycol fatty acid ester in the adhesive layer, a patch preparation having good adhesive properties (cohesive strength, water-resistant adhesion) and excellent skin permeability of the drug can be provided.
[0069] This application is based on patent application No. 2020-026339 filed in Japan on February 19, 2020, the contents of which are incorporated in their entirety herein.
Claims
1. A patch preparation having an adhesive layer on at least one surface of a support, A patch preparation, wherein the adhesive layer contains a basic drug having a basic group, levulinic acid, and propylene glycol monocaprylate or propylene glycol monolaurate, with the proviso that the drug does not include tandospirone or a pharma- ceutically acceptable salt thereof.
2. The patch preparation according to claim 1, wherein the adhesive layer further comprises a fatty acid ester other than propylene glycol monocaprylate or propylene glycol monolaurate.
3. The patch preparation according to claim 2, wherein the other fatty acid ester is at least one selected from the group consisting of an ester of an alcohol having a linear or branched alkyl group or a cyclic alkyl group having 1 to 18 carbon atoms and a saturated or unsaturated fatty acid having 8 to 18 carbon atoms, and an ester of glycerin and a saturated or unsaturated fatty acid having 8 to 18 carbon atoms.
4. The patch preparation according to any one of claims 1 to 3, wherein the content of the propylene glycol monocaprylate or propylene glycol monolaurate in 100% by mass of the adhesive layer is 1 to 30% by mass.
5. The patch preparation according to any one of claims 1 to 4, wherein the content ratio of levulinic acid to propylene glycol monocaprylate or propylene glycol monolaurate is 1:0.1 to 1:20 by mass ratio.
6. The patch preparation according to claim 5, wherein the content ratio of levulinic acid to propylene glycol monocaprylate or propylene glycol monolaurate is 1:0.5 to 1:10 by mass ratio.
7. The patch preparation according to any one of claims 1 to 6, wherein an adhesive base constituting the adhesive layer is an acrylic polymer.
8. The patch preparation according to claim 7, which contains N-vinyl cyclic amide as a monomer component constituting the acrylic polymer.
9. The patch preparation according to any one of claims 1 to 8, wherein the logPow of the drug is -1 to 7.
Citation Information
Patent Citations
Cataplasm
JP1995247221A
Preparation for percutaneous absorption
JP1998251145A
Transdermal adhesive composition containing poorly soluble therapeutic agent
JP2018518502A
Transdermal absorption patch
WO2006082728A1